Pediatric candiduria, epidemiology, genotype distribution and virulence factors of Candida albicans. (November 2021) - Gharaghani, Maral; Rezaei-Matehkolaei, Ali; Hardani, Amir Kamal; Zarei Mahmoudabadi, Ali
Abstract: The presence of Candida species in urine may be due to colonization of this species in the bladder, urinary catheter, and perineum. Candida albicans has been the most commonly isolated from urine samples in patients with candiduria. Several virulence factors include adhesion to host cells, secreted extracellular enzymes, phenotype switching, and biofilm formation are contributing to the pathogenicity of C. albicans . ABC genotyping is the method based on the determination of 25s rDNA and C. albicans is divided into four genotypes include A, B, C, and E. We aimed to identify Candida species from pediatrics and evaluate extracellular enzyme activities, phenotype switching, biofilm formation, and genotyping in isolates. Urine samples collected, cultured, and yielded yeasts were identified. Phenotype switching, biofilm formation, enzymatic patterns, and genotyping of 50 isolates of C. albicans were evaluated. The Genotyping pattern was compared with extracellular enzymes, biofilm formation, and phenotype switching pattern. 16.2% of urine cultures were positive for the different Candida species. The most common species was C. albicans, followed by C. glabrata . Out of 50 isolates of C. albicans, 72% and 28% isolates were recognized as genotypes A and C. All isolates were produced extracellular enzymes and biofilm formation. In conclusion, candiduria with high colony counts is still a challenge in Iranian pediatrics. Genotype A was the predominant genotype among C. albicans strains. There is a statistical difference between esterase and genotypes of C and A C. albicans . Graphical abstract: Image 1 Highlights: Candida albicans was common in urine samples. Non- albicans species, especially C. glabrata, account for a considerably high rate. Genotype A was the predominant genotype among C. albicans strains with the highest rates of 90:10 (A:C) in the neonatal intensive care unit. There are no statistical differences between extracellular enzymes and biofilm formation with genotypes of C and A C. albicans.